The extent of compliance of the Barangays in District IV, Quezon City with the Republic Act no. 7743 - Narvaez, Laurence Anthony G. (2011)
Public libraries are invaluable because they allow free and unlimited access to information by the general public regardless of race, gender, economic status, education and age. Specifically, Barangay Reading Centers (BRC) play an important role in providing the information needs of the people of the community they serve. This study aimed to find out the extent of compliance of the Barangays in District IV of Quezon City to the provision of Rep. Act No. 7743 and come up with information that can serve as a reference for the barangays with or without existing BRCs to fully comply with the law and further improve their existing collections, services and personnel.